Conventional Rehabilitation of Edentulous Patients: The Impact on Oral Health-Related Quality of Life and Patient Satisfaction - Janice S. Ellis, PhD, BDS, FDS RCS, PGCE;1 Nanita D. Pelekis, DDP, MSc;2 (Journal of Prosthodontics, 2007)
This study examined patient satisfaction and oral health-related impacts on the quality of life of patients restored with complete conventional or duplicate dentures.